Mundell-Fleming Model: The Effectiveness of Indonesia’s Fiscal and Monetary Policies - K, Nurjannah Rahayu; Putri, Phany Ineke (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This study examines the fiscal and monetary policy in Indonesia using the Mundell-Fleming model. The main objective of this study was to determine which policies are effective between fiscal and monetary policies of the national income in Indonesia because Indonesia is a small open economy with not perfect capital mobility. The analysis technique used is Two Stage Least Square (TSLS) by using secondary data base on International Financial Statistics, 2000.I – 2014.II . The research result is monetary policy is more effective than the fiscal policy in which monetary policy multiplier at 0.0028 greater than fiscal policy multiplier 0.001316. The results are consistent with the theory of the Mundell-Fleming.